Evaluation of outcome relevance of quality indicators in the emergency department (ENQuIRE): study protocol for a prospective multicentre cohort study - Anna Slagman; Felix Greiner; Martin Möckel; Rainer Röhrig; Susanne Drynda; Wencke Schindler; Johannes Pollmanns; Dirk Horenkamp-Sonntag; Wiebke Schirrmeister; Ronny Otto; Jonas Bienzeisler; Saskia Drösler; et al. (BMJ Open)
Introduction Quality of emergency department (ED) care affects patient outcomes substantially. Quality indicators (QIs) for ED care are a major challenge due to the heterogeneity of patient populations, health care structures and processes in Germany. Although a number of quality measures are already in use, there is a paucity of data on the importance of these QIs on medium-term and long-term outcomes. The evaluation of outcome relevance of quality indicators in the emergency department study (ENQuIRE) aims to identify and investigate the relevance of QIs in the ED on patient outcomes in a 12-month follow-up.Methods and analysis The study is a prospective non-interventional multicentre cohort study conducted in 15 EDs throughout Germany. Included are all patients in 2019, who were ≥18 years of age, insured at the Techniker Krankenkasse (statutory health insurance (SHI)) and gave their written informed consent to the study.The primary objective of the study is to assess the effect of selected quality measures on patient outcome. The data collected for this purpose comprise medical records from the ED treatment, discharge (claims) data from hospitalised patients, a patient questionnaire to be answered 6–8 weeks after emergency admission, and outcome measures in a 12-month follow-up obtained as claims data from the SHI.Descriptive and analytical statistics will be applied to provide summaries about the characteristics of QIs and associations between quality measures and patient outcomes.Ethics and dissemination Approval of the leading ethics committee at the Medical Faculty of the University of Magdeburg (reference number 163/18 from 19 November 2018) has been obtained and adapted by responsible local ethics committees.The findings of this work will be disseminated by publication of peer-reviewed manuscripts and presentations as conference contributions (abstracts, poster or oral presentations).Moreover, results will be discussed with clinical experts and medical associations before being proposed for implementation into the quality management of EDs.Trial registration number German Clinical Trials Registry (DRKS00015203); Pre-results.